Studi In Silico Bioaktivitas Antikanker Senyawa Aktif Dalam Minyak Biji Buah Wali [Brucea javanica (L.) Merr] - Agus Dwi Ananto; Handa Muliasari; Candra Dwipayana Hamdin (Sasambo Journal of Pharmacy, 2020)
Insilico study of anticancer bioactivity in oil of “buah wali” [Brucea javanica (L.) Merr] has been successfully carried out. “Buah Wali” (Brucea javanica (L.) Merr) is known to treat various diseases such as diabetes, diarrhea, and malaria. In addition, “buah wali” seeds are supported to have antidiabetic, antioxidant, and anticancer activities. The stages of the study began by taking a sample of “buah wali”seeds, then extracted to get oil of “buah wali”. While GC-MS analysis resulted Octadec-9-enoic acid (56.25%), palmitic acid (13.82%), stearic acid (10.57%), and acids -9-octadecanoate (5.91%) were found as the major components of the seed oil. Based on these compounds, docking molecular was carried out to find anticancer bioactivity. The results obtained are compounds that have lower binding energy than the native ligands [Octadec-9-enoic acid (-72.4518), hexadecanoic acid (-70.2136), octadecanoic (-72.2362).